2007
DOI: 10.3200/aeoh.62.1.5-11
|View full text |Cite
|
Sign up to set email alerts
|

Health Survey of Residents Living Near Farm Fields Permitted to Receive Biosolids

Abstract: The authors studied the health status of residents living in Wood County, OH, near farm fields that were permitted to receive biosolids. They mailed a health survey to 607 households and received completed surveys from 437 people exposed to biosolids (living on or within 1 mile of the fields where application was permitted) and from 176 people not exposed to biosolids (living more than 1 mile from the fields where application was permitted). The authors allowed for up to 6 surveys per household. Results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…Most prior research on environmental health risks has focused on urban populations 5,7 . Rural populations, however, are potentially exposed to a variety of serious environmental risks from point and non‐point pollution sources including industrial facilities, animal containment facilities, mining operations, agricultural activities, and others 8–12 . For example, the rural counties of eastern North Carolina have the highest childhood lead poisoning rates in the state 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most prior research on environmental health risks has focused on urban populations 5,7 . Rural populations, however, are potentially exposed to a variety of serious environmental risks from point and non‐point pollution sources including industrial facilities, animal containment facilities, mining operations, agricultural activities, and others 8–12 . For example, the rural counties of eastern North Carolina have the highest childhood lead poisoning rates in the state 9 .…”
mentioning
confidence: 99%
“…sources including industrial facilities, animal containment facilities, mining operations, agricultural activities, and others. [8][9][10][11][12] For example, the rural counties of eastern North Carolina have the highest childhood lead poisoning rates in the state. 9 Exposure to agricultural pesticides has adverse impacts on reproductive health and outcomes.…”
mentioning
confidence: 99%
“…A synopsis of the results is highlighted here with the rest of the results available from Khuder et al (2007). Of the survey participants, there was no significant difference with regard to age, gender, length of time living on the farm, percentage of time each spent at the address, high-risk occupations, and smoking status between the participants near the permitted fields and those greater than one mile away.…”
Section: Resultsmentioning
confidence: 90%
“…This project led to the publication of an epidemiological study conducted in Wood County of people living near agricultural fields permitted to receive biosolids (Khuder et al 2007). The GIS described herein was developed in ArcGIS in support of the Khuder et al (2007) epidemiological study.…”
Section: Methodsmentioning
confidence: 99%
“…According to Herr et al [15][16], the respiratory ailments occur primarily due to microbiological air pollution (exposure solely to odour does not cause health disorders). Other authors (including Khuder et al [17]) explained the increase in the number of reported diseases in the presence of a noticeable, irritating odour as anxiety (psychosomatic) responses of people afraid of poisoning.…”
Section: Discussionmentioning
confidence: 99%